2010
DOI: 10.1093/annonc/mdq032
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model in patients treated for metastatic gastric cancer with second-line chemotherapy

Abstract: With inadequate data from randomized controlled trials at the moment, our report indicates that second-line chemotherapy is effective and beneficial in patients with good performance status, higher Hb level along with higher TTP under first-line therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 19 publications
1
44
3
4
Order By: Relevance
“…2 Progression-free survival and overall survival curves according to the risk groups: a progression-free survival; b overall survival studies analyzed the prognostic factors for MRGC patients undergoing second-line chemotherapy. A good PS was the most important prognostic factor of second-line chemotherapy in nearly all studies [6,[23][24][25]; in addition, a higher hemoglobin level [23][24][25], longer PFS from firstline chemotherapy [6,23,25], and a lower number of metastatic sites [6,25] were reported as independent prognostic factors for OS. Shim et al [15] reported a prognostic factor analysis of third-line therapy; poor PS (ECOG PS C2), low serum albumin level (\4.0 g/dl), poor histological grade, and shorter PFS following second-line chemotherapy (\2.7 months) were factors related to poor survival outcome.…”
Section: Discussionmentioning
confidence: 96%
“…2 Progression-free survival and overall survival curves according to the risk groups: a progression-free survival; b overall survival studies analyzed the prognostic factors for MRGC patients undergoing second-line chemotherapy. A good PS was the most important prognostic factor of second-line chemotherapy in nearly all studies [6,[23][24][25]; in addition, a higher hemoglobin level [23][24][25], longer PFS from firstline chemotherapy [6,23,25], and a lower number of metastatic sites [6,25] were reported as independent prognostic factors for OS. Shim et al [15] reported a prognostic factor analysis of third-line therapy; poor PS (ECOG PS C2), low serum albumin level (\4.0 g/dl), poor histological grade, and shorter PFS following second-line chemotherapy (\2.7 months) were factors related to poor survival outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Chau et al [19] pooled data on 1080 patients from three randomized first-line trials and demonstrated that PS C 2, the presence of liver and/or peritoneal metastases, and elevated alkaline phosphatase were prognostic factors correlated with poor outcome in the first-line setting. Subsequent analyses evaluating patients receiving different regimens of chemotherapy in the second-line setting have described PS C 2, number of metastatic sites, short TTP under first-line chemotherapy, and different laboratory test results, such as low hemoglobinand elevated WBC or alkaline phosphatase as prognostic factors associated with overall survival [24][25][26][27]. Today the use of molecular targeting agents is a new challenge in modern cancer therapy and these agents may have a significant impact on the treatment of GEC patients in the future [28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to predict whether patients may benefit from sequential salvage chemotherapy. Previous studies have indicated that several factors should be considered in order to assess the response to sequential salvage chemotherapy, such as the performance status of the patient, extent of disease (locally advanced or metastatic), cumulative toxicity, lack of cross-resistance of the tumor cells to previously used drugs and progression-free survival of the patient following previous chemotherapy (26,30). Therefore, predictive factors for the potential survival benefit of salvage chemotherapy with active cytotoxic agents require additional investigation to avoid the development of toxic effects in patients that are unlikely to benefit from the therapy.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%